Modeling and simulation of parallel DC/DC converters for online AC impedance estimation of PEM fuel cell stack. (30th January 2016) - Hong, Po; Li, Jianqiu; Xu, Liangfei; Ouyang, Minggao; Fang, Chuan
Abstract: The electrochemical impedance spectroscopy (EIS) technique is now widely used in the study of the hydrogen polymer electrolyte membrane fuel cell (PEMFC), especially the diagnosis of flooding and drying. Though the working conditions of fuel cell vehicles is fairly rough with large electromagnetic interference and ever-changing environment, lots of efforts have been made to prompt the online EIS analysis of PEMFC stack in vehicles, such as using a DC/DC converter based on the ripple currents or active voltage control and so on. Considering the practical topologies of fuel cell powertrain systems, their researches inspire us to put forward a simpler approach in terms of applicability and controllability. For this reason, a topology of two parallel boost DC/DC converters for online AC impedance estimation of PEMFC stack is proposed. This topology is modeled using Matlab/Simulink. To better understand the electrical characteristic of PEMFC, equivalent circuits are utilized to model the PEMFC based on the electrochemical reactions and mass transport properties in the fuel cell. Fluctuation signals produced by a DC/DC converter are injected into the stack. The other DC/DC converter is used to adjust the output characteristic of the stack to the output voltage and current requirements of the external power devices and load. In this way, the fluctuation signal generation and power conversion are decoupled, which is more suitable for different applications of PEMFC stack. To effectively control these converters, closed-loop PI controllers are adopted and coefficients are regulated according to the frequency of disturbance signals. Based on this model, simulation results show that fluctuation signals are well generated and injected into the stack with low total harmonic distortion (THD). After analysis of the output voltage and current of the stack using FFT technique, AC impedance calculated is in consistent with the impedance characteristic of the equivalent circuits with high accuracy. Highlights: A parallel DC/DC converter topology was put forward for online AC impedance identification of PEMFC stack. The equivalent circuit model of PEMFC and DC/DC model were setup for validation. The frequency range of impedance was from 0.1 Hz to 1000 Hz. The analysis result of simulation matched well with the theoretical.